ISOLASI DAN UJI PATOGENITAS JAMUR Colletotrichum spp. PENYEBAB PENYAKIT ANTRAKNOSA PADA BUAH TOMAT (Solanum lycopersicum L.) : ISOLATION AND PATHOGENITY TESTING OF FUNGI Colletotrichum spp. CAUSES OF ANTHRACNOSE DISEASE ON TOMATOES (Solanum lycopersicum L.) - Laila Maghfirotun Ni’mah; Sang Ketut Sudirga; Anak Agung Ketut Darmadi (Program Studi Biologi Universitas Udayana, 2025)
Tomatoes (Solanum lycopersicum L.) is a fruit with important economic value and is a leading horticultural commodity in Indonesia. Anthracnose is a disease that can infect tomato plants. From previous research, several types of isolates of Colletotrichum spp. Infecting different hosts can cause different disease severity. The aim of this research was to identify the Colletotrichum fungus that causes anthracnose on tomatoes from several gardens in Bali to test its level of pathogenicity. Isolation of the fungus Colletotrichum spp. using the direct planting method. The pathogenicity test uses the disease severity (KP) scoring method using the formula. Identification and morphological characterization of isolates of Colletotrichum spp. using the identification book